KEPEMIMPINAN BERBASIS ISLAMI DALAM MENINGKATKAN MUTU PENGELOLAAN PERGURUAN TINGGI - Astuti Astuti; Saril Saril (Adaara: Jurnal Manajemen Pendidikan Islam, 2020)
This study discusses Islamic-based leadership in improving the quality of Higher Education management at IAIN Bone and IAIN Pare-Pare. The problems examined in this research are: (a) How is the Islamic-based leadership approach in improving the quality of Higher Education management at IAIN Bone and IAIN Pare-Pare, (b) How is the quality of Higher Education in IAIN Bone and IAIN Pare-Pare. The results showed that the Islamic-based leadership approach in improving the quality of Higher Education management at IAIN Bone and IAIN Pare-Pare applied Islamic values both in decision making, division of labor, direction, communication, giving awards, and giving sanctions. The values applied in the development of Higher Education management at IAIN Bone and IAIN Pare-Pare such as; trustworthy, honesty, respect, deliberation, consistency/discipline, commitment in carrying out duties and responsibilities, gentle, firm. humanist, firm attitude, meticulous, hard work, guiding, and always motivating. Likewise, the Islamic culture which is always used as the basis for the management of tertiary institutions, especially in IAIN Pare-Pare, is the malebbi warekkadana makkeade ampena (polite in speaking and ethical behavior). While at IAIN Bone is sipakatau (mutual respect, view humans as humans), sipakalebbi (mutual respect), and sipakainge (remind each other) in accordance with the values contained in IAIN Bone's vision. The quality of IAIN Bone and IAIN Pare-Pare higher education has improved from various aspects but after the transfer of status and changes in the standard of tertiary education it is always making improvements to adjust.